The liturgy of the in-between - Adiprasetya, Joas (Scottish journal of theology, 2019)
By using the idea of theology as symbolic engagement, I propose the 'in-between' as a liturgical category that engages with multiple tensions in Christian theology. The concept of the in-between becomes the primary lens through which to analyse not only the relationship between ecclesial and social liturgies, but also the interstices between the two. I then apply the concept to construct theological imagination in the ministries of ushering, intercessory prayer and the sending. The article concludes with a story of the worship of the GKI Yasmin church in front of the presidential palace in Indonesia, which demonstrates the prophetic dimension of the in-between.